Collisional cooled Ps emitted into vacuum from silica-based porous materials: experiment to measure the Ps cooling time. (May 2015) - Mariazzi, S; Noto, L Di; Nebbia, G; Brusa, R S
Abstract: In recent experiments on positronium time of flight (Ps-TOF) we have studied emission of cooled and thermalized Ps into vacuum from oxidized nanochannels synthetized in silicon. Ps cools down through collisions with the walls of the channels before exiting into vacuum. An important unknown parameter in the Ps-TOF measurements is the permanence time in the medium, i.e. the Ps cooling time before emission into vacuum. In this paper we describe an experiment that allows us to estimate the cooling time of Ps by analyzing the Ps- TOF spectra of cool Ps at three different distances from the sample.